Nonperforming loans in Asia: Determinants and macrofinancial linkages - Junkyu Lee; Peter Rosenkranz (Asian Development Bank (ADB), 2019)
The recent rise of nonperforming loans (NPLs) in some Asian economies calls for close analysis of the determinants, the potential macrofinancial feedback effects, and the implications for financial stability in the region. Using a dynamic panel model, we assess the determinants of the evolution of bankspecific NPLs in Asia and find that macroeconomic conditions and bank-specific factors - such as rapid credit growth and excessive bank lending - contribute to the buildup of NPLs. Further, a panel vector autoregression analysis of macrofinancial implications of NPLs in emerging Asia offers significant evidence for the feedback effects of NPLs on the real economy and financial variables. Impulse response functions demonstrate that a rising NPL ratio decreases gross domestic product growth and credit supply and increases unemployment rate. Our findings underline the importance of considering policy options to swiftly and effectively manage and respond to a buildup of NPLs. The national and regional mechanisms underlying NPL resolution are important for safeguarding financial stability in an increasingly interconnected global financial system.
Keywords: C32; C33; E44; G21; O16; 330; dynamic panel model; emerging Asia; financial stability; macrofinancial feedback effects; nonperforming loans; panel vector autoregression model